Implementation of Refined Hyperview of Learning (rHOL) on Management Accounting Learning Process (An Extended Ethnographic Study) - Ari Kamayanti; Aji Dedi Mulawarman (The Indonesian Journal of Accounting Research, 2013)
The purpose of this paper is to provide evidence on the implementation of Love-Based Accounting Education (LBAE) through refined Hyperview of Learning (rHOL) as the core of humanity learning process. The essence of rHOL is a purification process. We show the impact of rHOL on learning process by suiting faith towards God to free accounting education from secularism and corporate hegemony. Utilizing sing extended ethnography by phenomenology, we portray the implication of rHOL on accounting students’ learning conceptions on three management accounting topics: Activity-Based Costing, Total Quality Management, and Balanced Score Card. We name this method as exethnography. We argue that these three topics are secular and their existences are merely to support corporate hegemony.The presence of secularism and corporate hegemony has caused the abandonment of local values and local needs respectively. Educators play an important role in implementing rHOL since he/she must trigger and maintain the purification process throughout the learning process. The results are astonishing since there are shifts in students’ consciousness in three varying degrees (verstehen, critical, reconstruction/deconstruction). As a result of rHOL implementation, both the educator and the students were seen enlightened. They renew their consciousness and return to local values and local needs.